Factors associated with the appropriate use of ultra-broad spectrum antibiotics, meropenem, for suspected healthcare-associated pneumonia. Issue 40 (8th October 2021) - Kirsch, Nathan; Ha, Jane; Kang, Hee-Taik; Frisch, Tina; Yoo, Ji Won; Grossman, Craig; Oroomchi, Neema; Shigemitsu, Hidenobu; Cross, Chad L.; Kioka, Mutsumi John
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Pneumonia is a common disease-causing hospitalization. When a healthcare-associated infection is suspected, antibiotics that provide coverage for multi-drug resistant (MDR) or extended-spectrum beta-lactamase (ESBL) bacteria are frequently prescribed. Limited data is available for guidance on using meropenem as a first-line empiric antimicrobial in hospitalized patients with risk factors for MDR/ESBL bacterial infections. This was a single-center, retrospective study designed and conducted to identify factors associated with positive cultures for MDR/ESBL pathogens in hospitalized patients with suspected healthcare-associated pneumonia. Of the 246 patients, 103 patients (41%) received meropenem. Among patients prescribed meropenem, MDR/ESBL pathogens were detected in only 20 patients (13%). Patients admitted from a skilled nursing facility/long-term acute care (SNF/LTAC) or with a history of a positive culture for MDR/ESBL pathogens were significantly associated with positive cultures of MDR/ESBL pathogens during the hospitalization (odds ratio [95% confidence intervals], 31.40 [5.20–189.6] in SNF/LTAC and 18.50 [2.98–115.1] in history of culture-positive MDR/ESBL pathogen). There was no significant difference in mortality between the 3 antibiotic groups. Admission from a SNF/LTAC or having a history of cultures positive for MDR/ESBL pathogens were significantly associated with a positive culture for MDR/ESBL pathogens during the subsequent admission. We did not detect significant association between meropenem use as a first-line drug and morbidity and mortality for patients admitted to the hospital with suspected healthcare-associated pneumonia, and further prospective studies with larger sample size are needed to confirm our findings.